Investigation of linear periodically time-varying circuits based on their frequency characteristics - Shapovalov, Yuriy; Bachyk, Dariya; Piwowar, Anna (Archives of Electrical Engineering (Online), 2025)
Linear circuits with constant parameters are typically analysed based on their frequency characteristics, assuming the invariance of harmonic signals as they pass through the system. However, in linear periodically time-varying circuits, this invariance does not hold. The output signal in such circuits is a periodic signal composed of harmonic compo-nents at various frequencies determined by both the input signal and the periodic variation of the circuit parameters. This results in a frequency spectrum that includes harmonics be-yond the frequency of the input signal, influenced by the interaction between the input and the parameter variations. This paper investigates the behaviour of parametric devices by examining specific frequency ratios between the input signal and the variation in circuit parameters. The results are demonstrated using a parametric amplifier model and a long transmission line, analysed in the frequency domain.